ANALYSIS OF THE EFFECT OF HEAT INPUT VARIATIONS ON THE SMAW HARDFACING PROCESS USING NANOMETAL FILLERS TO THE MECHANICAL PROPERTIES OF WELDING METALS - Wardoyo, Toto
One of the significant developments in the industrial world is hardfacing techniques through the welding process. With this technique, the service life of components can be better which has resistance to wear problems, erosion, corrosion, and abrasion but still at competitive cost. Various studies have been conducted to improve the quality of these welding results. One thing that is done is the using of nano metal in welding, both as an electrode and as a filler. And from several studies that have been conducted showing metal welding with the use of nanometal has increased the value of weld metal hardness, improve the properties of welding results and reduce the defects.